Protein phosphatase 2A confers susceptibility to autoimmune disease through an IL-17-dependent mechanism() - Crispín, José C. (2012)
The contribution of individual molecular aberrations to the pathogenesis of systemic lupus erythematosus (SLE), an autoimmune disease that affects multiple organs, is often difficult to evaluate because of the presence of abundant confounding factors. To assess the effect of increased expression of the phosphatase PP2A in T cells, as recorded in SLE patients, we generated a transgenic mouse that overexpresses the PP2Ac subunit in T cells. The transgenic mouse displays a heightened susceptibility to immune-mediated glomerulonephritis in the absence of other immune defects. CD4(+) T cells produce increased amounts of IL-17 while the number of neutrophils in the peripheral blood is increased. IL-17 neutralization abrogated the development of glomerulonephritis. We conclude that increased PP2Ac expression participates in SLE pathogenesis by promoting inflammation through unchecked IL-17 production and facilitating the development of end-organ damage.